2004
DOI: 10.1161/01.res.0000133680.87668.fa
|View full text |Cite
|
Sign up to set email alerts
|

Activated Protein C Induces Endothelial Cell Proliferation by Mitogen-Activated Protein Kinase Activation In Vitro and Angiogenesis In Vivo

Abstract: Abstract-Activated protein C (APC), a natural anticoagulant, has recently been demonstrated to activate the mitogenactivated protein kinase (MAPK) pathway in endothelial cells in vitro. Because the MAPK pathway is implicated in endothelial cell proliferation, it is possible that APC induces endothelial cell proliferation, thereby causing angiogenesis. We examined this possibility in the present study. APC activated the MAPK pathway, increased DNA synthesis, and induced proliferation in cultured human umbilical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
117
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 156 publications
(134 citation statements)
references
References 34 publications
14
117
1
2
Order By: Relevance
“…In the PROWESS trial, sepsis patients that were treated with APC have a steady-state level of 45 ng/ ml [45]. However, our overall goal was to characterize the mechanism of APC to promote cell migration and we used similar APC concentrations as in previous in vitro studies (0.5-50 μg/ml) [20,26,29]. Interestingly, levels of APC used in HUVEC experiments are closer to physiological concentrations of APC (0.1-10 μg/ml) (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the PROWESS trial, sepsis patients that were treated with APC have a steady-state level of 45 ng/ ml [45]. However, our overall goal was to characterize the mechanism of APC to promote cell migration and we used similar APC concentrations as in previous in vitro studies (0.5-50 μg/ml) [20,26,29]. Interestingly, levels of APC used in HUVEC experiments are closer to physiological concentrations of APC (0.1-10 μg/ml) (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Using zymogen PC, chemically inactivated DEGR-APC, and an active site mutant of APC (S195A) with the MDA-MB-231 cancer cells, one finding of our study showed that the active protease was needed to increase cell migration. Therefore, unlike the inhibitory role of APC with lymphocytes, the pro-migratory role of APC in the MDA-MB-231 cells requires the active site of the protease, most likely to bind and activate receptors, such as PAR-1 [20,21,26,30,31], and to activate extracellular matrix proteases, such as MMP-2 and MMP-9 [27,46,47]. It is possible that when bound to EPCR, APC may undergo modifications to its macromolecular substrate recognition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations